EDUKASI & PENERAPAN ALAT HANDWASHER TOUCHLESS PADA SMK GLOBAL PRIMA KABUPATEN BEKASI, JAWA BARAT - Mohamad Zaenudin; Yasya Khalif Perdana Saleh; Adhes Gamayel; Ade Sunardi; Dian Nugraha (Universitas Mataram, 2023)
In this COVID-19 pandemic season, there are still many people who tend to lack awareness in complying with health protocols, especially in terms of crowding and maintaining hand hygiene. Many innovations for hand washing facilities have been made in tourist places, restaurant toilets, malls, and even places of worship. However, during the current Covid-19 pandemic season, have these placements and tools been able to break the ropes of spreading the virus? The answer is that it is still not enough, because the hand washing place is still touched by many hands. Even though some have used automatic or touchless hand washing stations, the purchase of these tools is quite expensive among the surrounding community. Therefore, in this project we intend to break the rope of the spread of the coronavirus, by designing an economical touchless hand washing sink. Then, after the tool was completed, the grant process to the party in need, namely SMK Global Prima in Tambun Utara, Bekasi Regency, was carried out. Although on a small scale, we hope that this effort can be useful for the students involved, the partners of SMK Global Prima, and the community in general.